Projects and Realities of Forming a Great Eurasian Space - A. A. Akaev; I. F. Kefeli (Евразийская интеграция: экономика, право, политика, 2024)
Aim. Analyze three options for the development and construction of the Eurasian space (Russian, Chinese and Turkic) and identify the advantages and risks associated with both the expansion of integration processes and external influence on states that are members of coalitions of the nonWestern world.Tasks. To trace the evolution of supranational structural formations in the Eurasian space after the collapse of the Soviet Union and their appearance in declarations, agreements and other legal documents, starting with statements about “the formation and development of a common economic space, pan-European and Eurasian markets”.To identify the characteristic features of globalization of all spheres of human existence, which has given rise to the need to understand the “landscape of global risks”, “global existential catastrophe” as an event leading “to the end of the existence of our descendants”, which together determined the transition to the formation of nation states, geopolitical and geo-economic coalitions in the Greater Eurasia space (“Central Asian Five”, EEAS, SCO, CSTO, UTC).Results. The concept of three main projects for the construction of Greater Eurasia is substantiated: Russian, based on the revival of the Eurasian ideology of N. S. Trubetskoy, P. N. Savitsky and G. V. Vernadsky; the Chinese “Belt and Road”, aimed at transforming the idea of the Great Silk Road into a Community of a Common Destiny for Humanity; Turkic, claiming to recreate the Turkic civilization with the goal of “bringing world civilizations closer together” on the Eurasian continent.The author’s position is argued regarding the need to ensure coplanarity and unidirectionality of the three vectors of implementation of Eurasian projects with the consistency of political decisions and actions of the three poles of power in the Greater Eurasian space — Russia, China and Turkey.Conclusions. Currently, the coordination of political decisions and actions of the three poles of power in the Greater Eurasian space, taking into account the principles of convergence of national interests in interstate unions, global geopolitical processes of multi-agent interaction and global security strategy in a polycentric world, is becoming relevant.